Special issue: Towards New Transatlantic Transport Research: The STELLA-STAR Project on the Move - Black, William R; Nijkamp, Peter; Reggiani, Aura (European Journal of Transport and Infrastructure Research, 2006)
Mobility as a key feature of a modern society takes place at all geographic scales. The past decades have witnessed an enormous and unprecedented increase in the volume of intercontinental transport (e.g., between Europe and North-America, and between Asia and North-America) (Black and Nijkamp, 2002). Interestingly enough, a similar development is also present at a local level, where not only the activity radius is increasing, but also the frequency of trips. Geographically, our world is becoming less distant (resembling a ‘small world network’; see, e.g., Barabasi, 2002 and Watts, 1999) and more local and close-by, the so-called ‘global village’ (Poot, 2004).